2003
DOI: 10.1002/cbf.1031
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and antioxidant enzyme activities in experimental hypothyroidism

Abstract: Free radicals are now well known to damage cellular components. To investigate whether age and thyroid level affect peroxidation speed, we examined the levels of malondialdehyde and antioxidant enzyme activities in different age groups of hypothyroid rats. Hypothyroidism was induced in 30- and 60-day-old Wistar Albino rats by the i.p. administration of propylthiouracil (10 mg kg(-1) body weight) for 15 days. While malondialdehyde levels of 30- or 60-day-old hypothyroid rats were increased in liver, they were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
3
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 34 publications
9
45
3
3
Order By: Relevance
“…Plasma MDA levels with hyperthyroidism prior to treatment to be significantly higher than control group, with the levels decreasing after treatment [20]. Consistent with other studies [21,22], in our study MDA levels were higher in patients with hyperthyroidisms compared to control group ( heart, hepatic and brain tissue [23,24]. It is known that lipid peroxidation and generation of ROS leads to oxidative stress and damage.…”
Section: Resultssupporting
confidence: 90%
“…Plasma MDA levels with hyperthyroidism prior to treatment to be significantly higher than control group, with the levels decreasing after treatment [20]. Consistent with other studies [21,22], in our study MDA levels were higher in patients with hyperthyroidisms compared to control group ( heart, hepatic and brain tissue [23,24]. It is known that lipid peroxidation and generation of ROS leads to oxidative stress and damage.…”
Section: Resultssupporting
confidence: 90%
“…Thyroid abnormalities are also considered as physiological modulators of in vivo cellular oxidative stress. It is now well established that deficiency of thyroid hormones can lead to an oxidative stress condition in the liver and heart with a consequent lipid peroxidative response (Yilmaz et al, 2003). Further, hypothyroidism-induced dysfunction of the respiratory chain in the mitochondria leads to accelerated production of free radicals (i.e., superoxide anion, hydrogen peroxide, and hydroxyl radical as well as lipid peroxides), which consequently leads to oxidative stress (Venditti et al, 1997;Yilmaz et al, 2003;Carmeli et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that lipid peroxidation increase and an antioxidant level decrease in blood of hypothyroid patients (Dumitriu et al 1988). Moreover, it has been demonstrated that the MDA content in plasma, liver and muscle of hypothyroid patients is increased (Yilmaz et al 2003). Also, another finding has shown an increasing of lipid peroxidation in plasma, liver, heart, and muscle of PTU-induced hypothyroid rats.…”
Section: Discussionmentioning
confidence: 92%